Identification of virulence and antibiotic resistant gene in laboratory strains Streptococcus agalactiae / Muhammad Syafiq Abdul Aziz - Abdul Aziz, Muhammad Syafiq (2015)
Streptococcus agalactiae or Group B Streptococcus (GBS) is a causative agent for serious infection and neonatal sepsis that lead to neonatal morbidity and mortality. Previous study proved that the pathogenesis of Streptococcus agalactiae infection is complex and the severity can be predicted by the identification of the virulence factors encoded among others by the cps gene cluster coding of the Streptococcus agalactiae capsule. However, there is a lack of study done on the laboratory strains Streptococcus agalactiae. Study done stated that the laboratory strains are unable to fully represent microorganism that growth in the 'real-world' environment. This study is done to identify the virulence genes and antibiotic resistance genes in Streptococcus agalactiae isolates from laboratory reference strains. The laboratory strains Streptococcus agalactiae are sub-cultured into two different time frames in order to observe for any genetic drift or variations. The detection of the virulence gene 1mb, cylE, bca, scpB, and rib gene and antibiotic resistant genes ermB gene and tetO gene are done by using SYBR Green real-time PCR. All the samples from both short term and long term time frame were analyzed for the presence of the virulence and antibiotic resistant genes. The outcomes of the analysis indicate there were no genetic drifts or variants for 1mb, cylE bca, scpB gene even after a series of passage. The rib gene is undetermined for genetic variations or drift since not all the sample expressed the gene. The ermB gene and tetO gene analysis were undetermined since the results of the analysis are not specific. The comparison between clinical sample and laboratory strains show that the laboratory strains expressed the same virulence genes as the clinical samples. This study suggested that the used of real-time PCR are specific and sensitive methods that could be used to detect the virulence gene of Streptococcus agalactiae.